Reconsidering the role of money for output, prices and interest rates - Giovanni Favara; Paolo Giordani (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
New Keynesian models of monetary policy assign no role to monetary aggregates, in the sense that the level of output, prices, and interest rates can be determined without knowledge of the quantity of money. We evaluate the empirical validity of this prediction by studying the effects of shocks to monetary aggregates using an identified VAR. Shocks to monetary aggregates are isolated by means of identifying restrictions suggested by this class of models. Contrary to the theoretical predictions, shocks to broad monetary aggregates have substantial and persistent effects on output and prices.
Keywords: E31; E52; E58; 330; New-Keynesian models; LM shocks; VAR; Block-exogeneity; Neukeynesianische Makroökonomik; Produktion; Preis; Zins; Theorie